Tawhid As a Foundation in Bulding a Family (Analytical Study of Surah al-An'am verse 151 Based on the Book of Tafsir Ulama Nusantara) - Rahman, Ryan Arief; Chusna, Nala Alfia; Rosanti, Dyah Elisa; Da’i, Rahmat Ardi Nur Rifa; Syahrinal, Syahrinal (Proceeding International Conference on Religion, Science and Education, 2024)
This article aims to discuss tawhid as a foundation in building a family by referring to the book of tafsir ulama nusantara which focuses on surah al-An'am verse 151. With qualitative research methods with the type of literature research. So the researcher becomes Tafsir Al-Azhar, Tafsir Al-Misbah, and Tafsir An-Nur as his primary source and books, journals, and some writings that have relevance to the theme as secondary sources. To make it easier to reach conclusions, researchers use Content analysis with the method of discriptive discussion-analysis and tafsir maudhu'i. The result of the research is that tawhid is a principle and guideline in life activities as well as in the family. If all activities in the household are based on tawhid will result in a harmonious life, full of love and responsibility and oriented to worship. The path in building a family is marriage with "mitsaq ghalizan" as his holy vow.